Cardiovascular Risk Factors at Different Stages of Menopause: A Study among Bengali-Speaking Hindu Ethnic Group, India - Kar, Debasmita; Roy, Subho (Anthropological Review, 2025)
A reduction in the estrogen and progesterone levels during midlife leads to adverse changes in body fat distribution, insulin and lipid metabolism, and endothelial dysfunction; all of these increase the risk of cardiovascular disease (CVD). However, scholars are not unanimous on whether menopause enhances the CVD risk, independent of the normal process of aging and other confounding factors. Despite the cardio-protective effect of endogenous estrogen during their premenopausal years, the increased life expectancy of women exposes them to a greater lifetime risk of CVD compared to men. The aim of the present study was to understand the cardiovascular risk factors associated with different stages of menopause. This study was cross-sectional in nature and was carried out in the Howrah district of West Bengal, India. Two hundred and one participants were recruited for the study (Premenopausal 71, Perimenopausal 61, and Postmenopausal 69). Data on body fat distribution, blood glucose levels, and total cholesterol, blood pressure, and socio-demographic, menstrual and reproductive history, and lifestyle characteristics were obtained following standard protocols. Multivariate analysis of covariance was performed to understand how menopausal status impacted CVD risk factors after controlling the effects of the confounders. Menopausal status significantly predicted the CVD risk factors and body fat measures after removing the effects of the confounding variables, reinforcing the role of estrogen in the development of CVD. An overwhelming majority of the participants in our study have central obesity; so, this group is more prone to developing CVD in the near future. Future cross-cultural studies are required to understand how the link between menopause and CVD varies across different cultural groups and throughout the menopausal transition.